EFEKTIFITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN TRIGONOMETRY HAND TRICK TERHADAP HASIL BELAJAR SISWA BAB TRIGONOMETRI DI SMAN 10 SEMARANG - Widi Fatmawati; Sutrisno; M. Saifuddin Zuhri; Christina Purwaningsih (Universitas Muhammadiyah Kotabumi, 2023)
Trigonometry is a difficult chapter for some students, so teachers must be able to use learning models combined with learning media or a special tactic to be able to make students have a good understanding. The purpose of this researcg was to find out whether the Problem Based Learning model assisted by trigonometry hand tricks is better than the conventional learning model which usually used by teacher in class. This research using quantative approach with quasi experimental design. The data used in this study were data of result study trigonometry chapter from class X-1 as an experimental class and class X-3 as a control class in an educational unit, SMA Negeri 10 Semarang. The results of the SPSS-assisted independent T-test that have been applied in this study indicate that the calculated T value is less than the 5% significance level, there is 0.030 <0.05. This states that there is an average difference between the experimental class and the control class. Based on this it was concluded that the Problem Based Learning model assisted by trigonometry hand tricks is better than the conventional learning model with the lecture method. Keyword : Problem Based Learning, Trigonometry, result of study, Trigonometry hand trick